Noor iterations for asymptotically nonexpansive mappings in CAT(0) spaces - Niwongsa,Y. (Hikari Ltd., 2015)
In this paper, Δ and strong convergence theorems are established for the Noor iterations of asymptotically nonexpansive mappings in CAT(0) spaces. Our results extend and improve the recent ones announced by Dhompongsa and Panyanak [10], Nanjaras and Panyanak [25], Xu and Noor [29] and many others.